2016
DOI: 10.3390/ijms17060906
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Magnesium Ions on the Enzymatic Synthesis of Ligand-Bearing Artificial DNA by Template-Independent Polymerase

Abstract: A metal-mediated base pair, composed of two ligand-bearing nucleotides and a bridging metal ion, is one of the most promising components for developing DNA-based functional molecules. We have recently reported an enzymatic method to synthesize hydroxypyridone (H)-type ligand-bearing artificial DNA strands. Terminal deoxynucleotidyl transferase (TdT), a template-independent DNA polymerase, was found to oligomerize H nucleotides to afford ligand-bearing DNAs, which were subsequently hybridized through copper-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
(59 reference statements)
1
19
0
Order By: Relevance
“…The same result would also be observed if the 3’-modified primer fails to interact with the active center of TdT or it folds into unfavourable secondary structures as in the case of pyrene-2’-deoxynucleotide [ 26 ] or 2-methyl-3-hydroxypyridin-4(1 H )-one 2’-deoxynucleotide (dH) [ 74 ]. In our hands TdT does not extend the 4-thio-dU-elongated primer in the presence of deoxythymidine triphosphate (dTTP) (data not shown); a similar effect has been observed with dH [ 70 ].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The same result would also be observed if the 3’-modified primer fails to interact with the active center of TdT or it folds into unfavourable secondary structures as in the case of pyrene-2’-deoxynucleotide [ 26 ] or 2-methyl-3-hydroxypyridin-4(1 H )-one 2’-deoxynucleotide (dH) [ 74 ]. In our hands TdT does not extend the 4-thio-dU-elongated primer in the presence of deoxythymidine triphosphate (dTTP) (data not shown); a similar effect has been observed with dH [ 70 ].…”
Section: Resultssupporting
confidence: 71%
“…However in the presence of Co 2+ TdT uses the former as substrate for the incorporation and subsequent elongation while only a single incorporation of dPyr 4OH is observed ( Figure 2 , lanes 5 and 6). Recently, it was demonstrated that binding affinity of TdT to the 3’-end of ON modified with 3-hydroxy-4-pyridone-based nucleotides depended on the Mg 2+ concentration and caused formation of unfavourable secondary structure of 3’-terminus [ 70 ]. As a consequence after incorporation of single nucleotide further elongation was impeded.…”
Section: Resultsmentioning
confidence: 99%
“…[51] The choice of the metal ion for the TdT-mediated polymerization of modified nucleotides also varies from case to case. For instance, Mg 2 + is the preferred cofactor if hydroxypyridone-or nitroindole-modifiedn ucleotides are considered, [45,52] but Mn 2 + is preferred with dImTP 4 ( Figure 4) as as ubstrate [53] and Co 2 + is often sufficient for the incorporation of base-modified nucleotides. [46][47]…”
Section: Biochemical Properties and Requirementsmentioning
confidence: 99%
“…Indeed, the TdT accepts ah ydroxypyridonemodified nucleotide as as ubstrate and incorporates up to five modifications on both ssDNA primers and on DNA duplexes containing 3'-end overhangs.I nterestingly,t he efficiency of the tailing reaction can be improved by decreasing the concentration of the Mg 2 + cofactor, as this cofactor is assumed to cause unfavorable folding of the modified nucleotides,w hich impedes further polymerization. [52] The combination of Cu 2 + and modifiedd sDNA leads to the assembly of two duplexes throughm etal-base pair formation,w hereast he addition of ethylenediaminetetraacetic acid (EDTA) triggers the disassembly of these constructs ( Figure 5B). [119] So far,o nly the hydroxypyridone-modified nucleotide [119] as well as imidazole-containing nucleotides [53,120] have been evaluated as substrates for the TdT in the context of metal-base pair formation, but this approachi sc ertainly expected to gain momentum in the near future.…”
Section: Formation Of Metal-mediatedb Ase Pairsmentioning
confidence: 99%
“…Very recently, hydroxypyridone-bearing nucleotides were consecutively incorporated into DNA strands by utilizing a template-independent DNA polymerase. 74,75 The enzymatically synthesized ligandbearing oligonucleotides formed metallo-DNA duplexes through the formation of HCu II H base pairs. Toward future applications, the regulation of electrical conductivity of DNA duplexes was demonstrated by utilizing the HCu II H base pairing.…”
Section: Cu(ii)-mediated Base Pairingmentioning
confidence: 99%